Conversion of nanoscale topographical information of cluster-assembled zirconia surfaces into mechanotransductive events promotes neuronal differentiation. Issue 1 (December 2016) - Schulte, Carsten; Rodighiero, Simona; Cappelluti, Martino; Puricelli, Luca; Maffioli, Elisa; Borghi, Francesca; Negri, Armando; Sogne, Elisa; Galluzzi, Massimiliano; Piazzoni, Claudio; Tamplenizza, Margherita; Podestà, Alessandro; et al.
Abstract Background Thanks to mechanotransductive components cells are competent to perceive nanoscale topographical features of their environment and to convert the immanent information into corresponding physiological responses. Due to its complex configuration, unraveling the role of the extracellular matrix is particularly challenging. Cell substrates with simplified topographical cues, fabricated by top-down micro- and nanofabrication approaches, have been useful in order to identify basic principles. However, the underlying molecular mechanisms of this conversion remain only partially understood. Results Here we present the results of a broad, systematic and quantitative approach aimed at understanding how the surface nanoscale information is converted into cell response providing a profound causal link between mechanotransductive events, proceeding from the cell/nanostructure interface to the nucleus. We produced nanostructured ZrO2 substrates with disordered yet controlled topographic features by the bottom-up technique supersonic cluster beam deposition, i.e. the assembling of zirconia nanoparticles from the gas phase on a flat substrate through a supersonic expansion. We used PC12 cells, a well-established model in the context of neuronal differentiation. We found that the cell/nanotopography interaction enforces a nanoscopic architecture of the adhesion regions that affects the focal adhesion dynamics and the cytoskeletal organization, which thereby modulates the general biomechanical properties by decreasing the rigidity of the cell. The mechanotransduction impacts furthermore on transcription factors relevant for neuronal differentiation (e.g. CREB), and eventually the protein expression profile. Detailed proteomic data validated the observed differentiation. In particular, the abundance of proteins that are involved in adhesome and/or cytoskeletal organization is striking, and their up- or downregulation is in line with their demonstrated functions in neuronal differentiation processes. Conclusion Our work provides a deep insight into the molecular mechanotransductive mechanisms that realize the conversion of the nanoscale topographical information of SCBD-fabricated surfaces into cellular responses, in this case neuronal differentiation. The results lay a profound cell biological foundation indicating the strong potential of these surfaces in promoting neuronal differentiation events which could be exploited for the development of prospective research and/or biomedical applications. These applications could be e.g. tools to study mechanotransductive processes, improved neural interfaces and circuits, or cell culture devices supporting neurogenic processes.